Learning how to work in an interprofessional environment: how students transition to allied health professionals working interprofessionally. Issue 3 (4th May 2022) - Jones, L.; Fowler, D.; Bialocerkowski, A.; Sheeran, N.
ABSTRACT: Allied health professionals (AHPs) often work with other health professions to provide specialized support so that patients receive optimal care. Therefore, new graduate AHPs need to be able to engage collaboratively with various health professionals in the provision of health care services. This study examines new AHP graduates' experiences and reflections on the transition to working in an interprofessional environment. Participants were new graduates ( n = 18) from different universities, working in a hospital context, from occupational therapy, speech pathology, social work, pharmacy, and physiotherapy. Qualitative data were collected via two semi-structured interviews conducted over 12 months. The data were analyzed using thematic analysis, with three key themes emerging: (a) The role of the work context, 2) Learning to work interprofessionally, and 3) Developing an interprofessional identity. We discuss the implications for universities and workplaces in enhancing interprofessional practice and learning opportunities among new graduates.